2017
DOI: 10.3892/etm.2017.4058
|View full text |Cite
|
Sign up to set email alerts
|

Bupivacaine effectively relieves inflammation-induced pain by suppressing activation of the NF-κB signalling pathway and inhibiting the activation of spinal microglia and astrocytes

Abstract: Abstract. The pain induced by local acute inflammation results in mild to severe discomfort, in addition to the possibility of physiological dysfunction and psychiatric disorders, such as sleep disorders and depression. However, the pathogenesis of pain is yet to be fully elucidated. In the present study, the effects of bupivacaine were explored in rat models inflammatory pain in order to investigate the anti-pain mechanism of bupivacaine. Complete Freund's adjuvant (CFA) was injected into the right rear foot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…Among these cytokines, TNF-α and IL-6 are known to function as potent proinflammatory cytokines during the reperfusion period [6,27,28]. Consistent with our observation of bimodal allodynia induced during IR injury, two periods of robust TNF-α production were previously observed in an in vivo study [6].…”
Section: Discussionsupporting
confidence: 78%
“…Among these cytokines, TNF-α and IL-6 are known to function as potent proinflammatory cytokines during the reperfusion period [6,27,28]. Consistent with our observation of bimodal allodynia induced during IR injury, two periods of robust TNF-α production were previously observed in an in vivo study [6].…”
Section: Discussionsupporting
confidence: 78%
“…The NF-κB pathway is well known for its role in inflammation, the regulation of cell differentiation, and apoptosis. In the nervous system, the NF-κB-p65/p50 dimer is a prime inducer of pro-inflammatory genes ( 49 ). Sustained activation of NF-κB induces a cycle of microglial activation, that can result in brain parenchymal and neuronal damage.…”
Section: Discussionmentioning
confidence: 99%
“…No difference was observed in the other three groups. Notably, previous studies have shown that phosphorylation of IκBa is responsible for its dissociation from NF-κB, after which free IκBa is rapidly degraded ( 49 ). Herein, RT-qPCR and western blotting analysis found that IκBa mRNA and protein levels increased in the comorbidity group, suggesting the possibility that additional cellular events serve to activate NF-κB ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bupivacaine, a local anesthetic, has been proposed to attenuate inflammatory responses at concentrations much lower than those that block Na + channels [16,17]. Bupivacaine decreases the expression of nuclear factor (NF)-қB and proinflammatory cytokines such as tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β) and interleukin-6 (IL-6) [18]. Bupivacaine treatment in rat models of inflammatory pain decreased the activation of microglia and astrocytes [18].…”
Section: Introductionmentioning
confidence: 99%
“…Bupivacaine decreases the expression of nuclear factor (NF)-қB and proinflammatory cytokines such as tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β) and interleukin-6 (IL-6) [18]. Bupivacaine treatment in rat models of inflammatory pain decreased the activation of microglia and astrocytes [18].…”
Section: Introductionmentioning
confidence: 99%